The Court of Appeal in Northern Ireland - McCormick, Conor; Dickson, Brice (Bristol University Press, 2024)
Available open access digitally under CC-BY-NC-ND licence. The Court of Appeal in Northern Ireland has functioned without interruption for over a century, yet its intermediate position can obscure the importance of its judgments. This book demonstrates the Court of Appeal's pivotal role in securing justice, both by correcting lower court decisions and by developing the common law. It examines, in particular, how the Court has applied and developed the rule of law in a post-conflict society. Authored by experts in the law of Northern Ireland, this compelling text is based on archival research, statistical and qualitative case analyses, court observations, and exclusive interviews with senior judges.